Suppression of adrenomedullin contributes to vascular leakage and altered epithelial repair during asthma - Hagner, S.; Welz, H.; Kicic, Anthony; Alrifai, M.; Marsh, L.; Sutanto, E.; Ling, K.; Stick, S.; Müller, B.; Weissmann, N.; Renz, H. (2012)
Background The anti-inflammatory peptide, adrenomedullin (AM), and its cognate receptor are expressed in lung tissue, but its pathophysiological significance in airway inflammation is unknown. Objectives This study investigated whether allergen-induced airway inflammation involves an impaired local AM response. Methods Airway AM expression was measured in acute and chronically sensitized mice following allergen inhalation and in airway epithelial cells of asthmatic and nonasthmatic patients. The effects of AM on experimental allergen-induced airway inflammation and of AM on lung epithelial repair in vitro were investigated. Results Adrenomedullin mRNA levels were significantly (P < 0.05) reduced in acute ovalbumin (OVA)-sensitized mice after OVA challenge, by over 60% at 24 h and for up to 6 days. Similarly, reduced AM expression was observed in two models of chronic allergen-induced inflammation, OVA- and house dust mite-sensitized mice. The reduced AM expression was restricted to airway epithelial and endothelial cells, while AM expression in alveolar macrophages was unaltered. Intranasal AM completely attenuated the OVA-induced airway hyperresponsiveness and mucosal plasma leakage but had no effect on inflammatory cells or cytokines. The effects of inhaled AM were reversed by pre-inhalation of the putative AM receptor antagonist, AM (22-52) . AM mRNA levels were significantly (P < 0.05) lower in human asthmatic airway epithelial samples than in nonasthmatic controls. In vitro, AM dose-dependently (10 -11 -10 -7 M) accelerated experimental wound healing in human and mouse lung epithelial cell monolayers and stimulated epithelial cell migration. Conclusion Adrenomedullin suppression in T H 2-related inflammation is of pathophysiological significance and represents loss of a factor that maintains tissue integrity during inflammation. Â© 2012 John Wiley & Sons A/S.